EFFECTIVENESS OF APPLYING GENOGRAM TECHNIQUE TO INCREASE CAREER EFFICACY OF HIGH SCHOOL STUDENTS - Farida Aryani; Suciani Latif; Muhammad Rafli (JURNAL NALAR PENDIDIKAN, 2024)
This study aims to analyze the description of generation Z on career choices before applying the genogram technique, design an overview of the development of the genogram technique as a tool for determining generation Z career choices, and conduct a suitability test for applying the genogram technique in increasing generation Z career choices in Makassar city. This research was conducted in the city of Makassar on generation Z children. The approach used in this study was a quasi-experimental approach with a pretest-posttest control group design. Data analysis used descriptive statistics and t-test. The results showed that (1) the description of the Z generation's career choices before being given the genogram technique was in the low category. (2) The description of the implementation of the genogram technique for Generation Z was carried out in 3 meetings, as evidenced by the ability of students to show the results of the genogram. (3) The genogram technique is categorized as effective for increasing the career choices of generation Z students. Therefore, it can be written that the genogram technique can provide direction for career choices and support the development of students in determining effectively future careers.